Preparation method, product and application of organosilicon ceramic foam with controllable skin thickness

Through electronic irradiation and vulcanization processes, the silicone foam forms a thick skin and porous structure, which solves the problem of thin skin and easy damage at high temperatures, and achieves the ceramicized fire-proof and heat-insulating effect.

CN119661892APending Publication Date: 2025-03-21HUBEI XIANGYUAN NEW MATERIAL TECH INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411867020.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing silicone foam has thin skin and is easily damaged in high temperature environments, resulting in poor thermal insulation performance.

Method used

The silicone foam sheet is electron irradiated by an electronic accelerator to form a skin with controllable thickness, and an internal foam structure is formed by primary vulcanization and secondary vulcanization.

Benefits of technology

It achieves ceramicization, fire resistance and flame retardant at high temperatures, and maintains good thermal insulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661892A_ABST
    Figure CN119661892A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of organosilicon ceramic foam with controllable skin thickness, and belongs to the technical field of foam materials, raw materials are mixed and calendered into a sheet material, the sheet material is subjected to electron irradiation through an electron accelerator, a skin with the thickness of 0.1-0.5 mm is formed outside the sheet material, a foam structure is formed inside the sheet material through primary vulcanization and secondary vulcanization, and the organosilicon ceramic foam with the controllable skin thickness is obtained. And the organosilicone ceramic foam with controllable skin thickness is prepared. The invention further discloses a corresponding product and application. The organosilicone ceramic foam with the controllable skin thickness has proper compression stress at normal temperature, and can provide buffering and damping effects; when thermal runaway occurs, a compact ceramic layer structure is formed on the skin, fire prevention and flame retardance are achieved, the internal porous structure plays a role in heat insulation, and further heat transfer is slowed down.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of foam materials, and specifically relates to a preparation method of an organosilicon ceramic foam with controllable surface thickness, a product and an application thereof. Background Art

[0002] An insulating silicone foam is needed between the cells of the power battery, which can delay the transfer of heat in a high temperature environment and prevent thermal runaway of adjacent cells. Further, by adding porcelain fillers to the silicone foam, a ceramic structure can be formed at high temperature, which can play a role in fire protection while insulating. However, when preparing silicone foam in the prior art, the foaming reaction is completed first, and then it is quickly cured and formed, and the surface of the foam is thin. When the temperature is greater than 400°C, the silicone rubber begins to decompose. Since the surface of the foam is thin and easy to be damaged or perforated, the heat flow can quickly enter the interior of the foam. At this time, the thermal insulation performance of the foam cannot reach the ideal state. Therefore, there is a need for a material that can be both fireproof and maintain good thermal insulation performance in a high temperature environment. Summary of the invention

[0003] In response to one or more of the above defects or improvement needs of the prior art, the present invention provides a silicone ceramic foam with controllable surface thickness, which can be ceramicized at high temperature, is fire retardant, and has good thermal insulation effect.

[0004] To achieve the above-mentioned purpose, according to the first aspect of the present invention, a method for preparing an organosilicon ceramic foam with controllable skin thickness is provided, wherein the raw materials are mixed and rolled into a sheet, and the sheet is electron irradiated by an electron accelerator to form a skin with a thickness of 0.1 to 0.5 mm on the outside, and then a foam structure is formed inside through primary vulcanization and secondary vulcanization to obtain an organosilicon ceramic foam with controllable skin thickness.

[0005] As a further improvement of the present invention, the electron beam energy of the electron accelerator is 150-400 keV, and the irradiation dose is 150-400 kGy.

[0006] As a further improvement of the present invention, the temperature range of the primary vulcanization is 40 to 80° C., and the time of the primary vulcanization is 5 to 15 minutes.

[0007] As a further improvement of the present invention, the temperature range of the secondary vulcanization is 150-180° C., and the time of the secondary vulcanization is 20-60 minutes.

[0008] As a further improvement of the present invention, the raw materials include vinyl-terminated polydimethylsiloxane, ceramic filler, reinforcing filler, flame retardant, flux, foaming agent, catalyst, thixotropic agent, crosslinking agent, and inhibitor.

[0009] As a further improvement of the present invention, the raw materials include component A raw materials and component B raw materials, and the mixing mass ratio of the component A raw materials to the component B raw materials is 1:1;

[0010] The raw materials of component A include: 100 parts of vinyl-terminated polydimethylsiloxane, 40-60 parts of ceramic filler, 5-20 parts of reinforcing filler, 10-20 parts of flame retardant, 10-20 parts of flux, 5-30 parts of foaming agent, 0.2-2 parts of catalyst, and 0.1-0.5 parts of thixotropic agent;

[0011] The raw materials of component B include: 100 parts of vinyl-terminated polydimethylsiloxane, 40-60 parts of ceramic filler, 5-20 parts of reinforcing filler, 10-20 parts of flame retardant, 10-20 parts of flux, 10-20 parts of cross-linking agent and 0.02-0.2 parts of inhibitor.

[0012] As a further improvement of the present invention, the vinyl-terminated polydimethylsiloxane is a linear polymer with vinyl groups at both ends;

[0013] Preferably, the vinyl-terminated polydimethylsiloxane has a viscosity of 1000 to 100000 mPa·s at 25° C.

[0014] As a further improvement of the present invention,

[0015] The ceramic filler includes one or more of wollastonite, muscovite powder, kaolin, and diatomaceous earth; and / or,

[0016] The reinforcing filler comprises one or more of fumed silica, precipitated silica, and nano calcium carbonate; and / or,

[0017] The flame retardant includes one or more of magnesium hydroxide, aluminum hydroxide, and hydrotalcite; and / or,

[0018] The flux comprises one or more of low melting point glass powder and zinc borate; and / or,

[0019] The cross-linking agent is a hydrogen-containing silicone oil having at least three silicon-hydrogen bonds in one molecule; and / or,

[0020] The foaming agent includes one or more of hydroxy silicone oil, isopropanol, and ethanol; and / or,

[0021] The catalyst comprises one or more of chloroplatinic acid, a coordination compound of chloroplatinic acid and vinyl siloxane, alcohol-modified chloroplatinic acid, and a coordination compound of platinum and vinyl siloxane; and / or,

[0022] The inhibitor comprises one or more of 3-methyl-1-butyn-3-ol, 1-hexynyl-1-cyclohexanol, tetramethylvinylcyclotetrasiloxane; and / or,

[0023] The thixotropic agent is methyl silicone oil with a polyether structure in the side chain.

[0024] According to a second aspect of the present invention, there is provided an organic silicon ceramic foam with controllable surface thickness, which is prepared by the method for preparing the organic silicon ceramic foam with controllable surface thickness.

[0025] The thickness of the organic silicon ceramic foam is 1 to 4 mm; and / or,

[0026] The density of the organic silicon ceramic foam is 350-750 kg / m 3 and / or,

[0027] The Shore A hardness of the organic silicon ceramic foam is 10-30°.

[0028] According to a third aspect of the present invention, there is provided an application of the aforementioned organosilicon ceramic foam with controllable surface thickness in a power battery cell.

[0029] In general, the above technical solution conceived by the present invention has the following beneficial effects compared with the prior art:

[0030] (1) The preparation method of the silicone ceramic foam with controllable skin thickness of the present invention adopts the method of electron irradiation cross-linking, firstly irradiation cross-linking to solidify the skin, so that the silicone rubber skin forms a dense structure, and then the internal foaming and curing are carried out to form a foam structure inside, which can be ceramicized at high temperature, fireproof and flame retardant, and has good heat insulation effect. By controlling the electron beam energy of 150-400keV and the irradiation dose of 150-400kGy, the thickness of the skin is controlled to reach 0.1-0.5mm, so as to achieve more suitable fireproof performance and heat insulation performance at high temperature.

[0031] (2) The organosilicon ceramic foam with controllable surface thickness of the present invention has good functions of buffering and shock absorption and fireproofing and heat insulation. It has appropriate compressive stress at room temperature and can provide buffering and shock absorption. When thermal runaway occurs, the organosilicon ceramic foam with controllable surface thickness of the present invention can quickly form a dense ceramic structure layer on the surface to prevent the spread of flames. The internal porous structure plays a role of heat insulation, further preventing heat flow from entering the interior of the foam and slowing down heat transfer. Compared with traditional ceramic silicone foam, it has better thermal insulation performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a flow chart of a method for preparing an organic silicon ceramic foam with controllable surface thickness according to an embodiment of the present invention;

[0033] Figure 2 Schematic diagram of a flame impact test device in an embodiment of the present invention. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0035] The embodiment of the present invention provides a silicone ceramic foam with controllable surface thickness and a preparation method thereof, wherein the raw materials are mixed and rolled into a sheet, and the sheet is subjected to electron irradiation by an electron accelerator to form a surface with a thickness of 0.1 to 0.5 mm on the outside, and then a foam structure is formed inside by primary vulcanization and secondary vulcanization to obtain a silicone ceramic foam with controllable surface thickness. The silicone ceramic foam with controllable surface thickness of the embodiment of the present invention is particularly suitable for the battery cells of power batteries, and its surface thickness is 0.1 to 0.5 mm, can be ceramicized at high temperatures, is fire retardant, and has good heat insulation effect.

[0036] like Figure 1 As shown, the method for preparing the silicone ceramic foam with controllable surface thickness according to the embodiment of the present invention includes the steps of mixing raw materials, calendering, irradiation, vulcanization molding, etc. As a preferred embodiment of the present invention, specifically, it includes the following steps:

[0037] S1. Mix the raw materials evenly, extrude them between two release films, and calender them into sheets. Use an electron accelerator to irradiate both sides of the sheets with electrons. The electron beam energy of the electron accelerator is 150-400 keV, and the irradiation dose is 150-400 kGy, so that a skin with a thickness of 0.1-0.5 mm is formed on both sides of the sheets.

[0038] S2, subjecting the sheet material after electron irradiation in S1 to a vulcanization molding;

[0039] S3, peeling off the release film of the sheet material vulcanized once in S2, and subjecting the sheet material to secondary vulcanization and molding to obtain the organic silicon ceramic foam material with controllable surface thickness.

[0040] Preferably, the raw materials include component A raw materials and component B raw materials, and the mixing mass ratio of the two is 1:1. The component A raw materials include: 100 parts of vinyl-terminated polydimethylsiloxane, 40-60 parts of ceramic filler, 5-20 parts of reinforcing filler, 10-20 parts of flame retardant, 10-20 parts of flux, 5-30 parts of foaming agent, 0.2-2 parts of catalyst, and 0.1-0.5 parts of thixotropic agent;

[0041] The raw materials of component B include: 100 parts of vinyl-terminated polydimethylsiloxane, 40-60 parts of ceramic filler, 5-20 parts of reinforcing filler, 10-20 parts of flame retardant, 10-20 parts of flux, 10-20 parts of cross-linking agent, and 0.02-0.2 parts of inhibitor;

[0042] Preferably, in S2, the temperature range of the primary vulcanization is 40-80°C, and the time of the primary vulcanization is 5-15 minutes; in S3, the temperature range of the secondary vulcanization is 150-180°C, and the time of the secondary vulcanization is 20-60 minutes. The purpose of the primary vulcanization in S2 is to complete the foaming reaction and preliminary cross-linking, and the foaming reaction temperature is relatively low at this stage; the secondary vulcanization temperature in S3 is relatively high, so that the material is further cross-linked and completely cured. And through the primary vulcanization and secondary vulcanization, the residual vinyl in the epidermis will also participate in the cross-linking, further improving the hardness.

[0043] The present invention controls the thickness of the skin to 0.1 to 0.5 mm by controlling the electron beam energy to 150 to 400 keV and the irradiation dose to 150 to 400 kGy through the process of electron irradiation cross-linking, and further heats and sulfides the inside to complete the foaming and aging. Irradiation cross-linking solidifies the surface silicone of a certain thickness, and the cured rubber can no longer form bubbles. During vulcanization, the inside is foamed and formed, thereby distinguishing the skin layer from the internal foam layer. Compared with ordinary ceramic foamed silicone rubber, the thickness of the skin of the present invention is thicker. In a high temperature environment, the ceramic structure layer formed is denser, which blocks the heat flow from entering the foam, thereby achieving a better heat insulation effect.

[0044] When the thickness of the epidermis is lower than 0.1mm, the formed ceramic layer is not dense enough. Under high temperature impact, pores are easily formed, and the thermal insulation performance deteriorates. At the same time, the strength of the ceramic layer is low and it is easy to crack. When the thickness of the epidermis is higher than 0.5mm, under the condition of a certain total thickness, the thickness of the porous foam structure is too small and the thermal insulation performance will also deteriorate. At the same time, under high temperature, ceramics are quickly formed on the surface of the epidermis, but no ceramics are formed inside the epidermis, resulting in excessive temperature difference and easy cracking of the epidermis, which affects thermal runaway and thermal insulation effects.

[0045] Furthermore, the electron beam energy determines the penetration ability of the electron beam. By adjusting the electron beam energy, the thickness of the electron beam can be adjusted. When the electron beam energy is lower than 150keV, the penetration ability is weak, resulting in a surface thickness of less than 0.1mm; when the electron beam energy is higher than 400keV, the penetration ability is strong, and the surface thickness will be higher than 0.5mm. The irradiation dose determines the degree of curing of the rubber. If the irradiation dose is too low, the rubber is not cured and formed, and still has a certain plasticity, and the subsequent foaming process can still be carried out. At this time, the irradiation cross-linking does not play a curing role, so that the surface thickness is low; if the irradiation dose is too high, it will cause energy waste and even decomposition, resulting in easy cracking due to flame impact.

[0046] In addition, the present invention introduces ceramic inorganic fillers into the raw materials to give the foam the ability to ceramicize at high temperature; introduces a foaming agent to form a foam material with a porous structure inside; introduces a thixotropic agent to increase the interaction between the fillers, among which the effects of fumed silica and the thixotropic agent are particularly obvious, which can prevent the bubbles from growing and merging, making the pores small and numerous, and enhancing the thermal insulation effect.

[0047] In a preferred embodiment, the thickness of the organic silicon ceramic foam with controllable skin thickness of the present invention is 1 to 4 mm. When the thickness is less than 1 mm, the overall thermal insulation performance of the material is poor, and the skin does not play a significant role; when the thickness is greater than 4 mm, the overall thermal insulation performance of the material is very good, and the skin thickness has little effect.

[0048] In a preferred embodiment, the density of the organic silicon ceramic foam with controllable surface thickness of the present invention is 350-750 kg / m 3 , more preferably 450 to 650 kg / m 3 The density is tested according to the standard GB / T 6343-2009.

[0049] When the density of the silicone ceramic foam with controllable skin thickness is lower than 350kg / m 3 When the density of the silicone ceramic foam with controllable surface thickness is greater than 750kg / m 3 When , it indicates that the foaming ratio of the material is low, the gas contained inside is less, and the thermal insulation performance is poor.

[0050] In a preferred embodiment, the Shore A hardness of the organic silicon ceramic foam with controllable skin thickness of the present invention is 10-30°. If the hardness is too low, it means that the internal pores are large, not dense, and the thermal insulation performance is poor; if the hardness is too high, it means that the material density is large, the foaming ratio is low, and the thermal insulation performance is poor.

[0051] In a preferred embodiment, the organosilicon ceramic foam with controllable surface thickness of the present invention has a thickness of

[0052] When the thickness is ≥2mm, no cracks will appear on the back after ablation in acetylene plus oxygen flame at 1300℃ for 30min.

[0053] In a preferred embodiment, the organosilicon ceramic foam with controllable surface thickness of the present invention has a thickness of

[0054] When the thickness is ≥2mm, the hot surface is heated at 750℃ for 5min, and the cold surface temperature is ≤230℃. At present, the power battery on the market may cause open fire after thermal runaway, and the temperature exceeds 600℃. The organic silicon ceramic foam with controllable surface thickness of the present invention can effectively block the spread of heat and flames, protect adjacent batteries from thermal runaway in a short time, give drivers and passengers precious escape time, and ensure human life safety.

[0055] In some specific embodiments of the present invention, in the raw material composition of the above-mentioned silicone ceramic foam with controllable epidermal thickness, the vinyl-terminated polydimethylsiloxane is a linear polymer with vinyl groups at both ends. Preferably, the vinyl-terminated polydimethylsiloxane has a viscosity of 1000 to 100,000 mPa·s at 25°C and can be mixed with multiple viscosities. If the viscosity of the vinyl-terminated polydimethylsiloxane is lower than 1000 mP·s, the crosslinking degree increases rapidly during the curing process of the rubber, the material foaming ratio is low, and the thermal insulation performance is poor; if the viscosity is higher than 100,000 mP·s, the viscosity of the rubber is too high and the mixing process becomes difficult.

[0056] In some specific embodiments of the present invention, in the raw material composition of the above-mentioned organosilicon ceramic foam with controllable surface thickness, the ceramic filler is selected from at least one of wollastonite, muscovite powder, kaolin, and diatomaceous earth. Preferably, the ceramic filler is hydrophobically treated with a surface treatment agent and has a particle size of 1 to 10 μm. Further preferably, the surface treatment agent includes at least one of stearic acid, rosin acid, citronellal acid, and lauric acid.

[0057] In some specific embodiments of the present invention, in the raw material composition of the above-mentioned silicone ceramic foam with controllable surface thickness, the reinforcing filler is selected from at least one of fumed silica, precipitated silica, and nano calcium carbonate. Preferably, the reinforcing filler is fumed silica with a specific surface area of ​​100 to 300 m 2 / g.

[0058] In some specific embodiments of the present invention, in the raw material composition of the above-mentioned organosilicon ceramic foam with controllable surface thickness, the flame retardant is selected from at least one of magnesium hydroxide, aluminum hydroxide and hydrotalcite, and the particle size is preferably 1 to 20 μm.

[0059] In some specific embodiments of the present invention, in the raw material composition of the above-mentioned silicone ceramic foam with controllable surface thickness, the flux is selected from at least one of low-melting glass powder and zinc borate. Preferably, the flux is low-melting glass powder with a melting temperature of 400-600°C and a particle size of 1-10 μm.

[0060] In some specific embodiments of the present invention, in the raw material composition of the above-mentioned silicone ceramic foam with controllable skin thickness, the cross-linking agent is a hydrogen-containing silicone oil having at least 3 silicon-hydrogen bonds in one molecule. Preferably, the hydrogen content of the cross-linking agent is 1.2-1.6% and the molecular weight is 500-2000 g / mol.

[0061] In some specific embodiments of the present invention, in the raw material composition of the above-mentioned organosilicon ceramic foam with controllable surface thickness, the foaming agent is selected from at least one of hydroxy silicone oil, isopropanol, and ethanol. Preferably, in the hydroxy silicone oil, the side chain is methyl and the mass fraction of hydroxyl is 4% to 10%. The purity of the isopropanol and ethanol is greater than 99.5%.

[0062] In some specific embodiments of the present invention, in the raw material composition of the above-mentioned silicone ceramic foam with controllable surface thickness, the catalyst is selected from at least one of chloroplatinic acid, a coordination compound of chloroplatinic acid and vinyl siloxane, alcohol-modified chloroplatinic acid, and a coordination compound of platinum and vinyl siloxane, and the platinum content is preferably 3000-5000ppm. Preferably, the catalyst is chloroplatinic acid tetramethyl divinyl disiloxane complex, and the platinum content is 5000ppm.

[0063] In some specific embodiments of the present invention, in the raw material composition of the above-mentioned silicone ceramic foam with controllable surface thickness, the inhibitor is selected from at least one of 3-methyl-1-butyn-3-ol, 1-hexynyl-1-cyclohexanol, and tetramethylvinylcyclotetrasiloxane.

[0064] In some specific embodiments of the present invention, in the raw material composition of the above-mentioned silicone ceramic foam with controllable epidermal thickness, the thixotropic agent is a methyl silicone oil containing a polyether structure in the side chain, and the viscosity at 25°C is 50-500mPa·s. Preferably, the thixotropic agent is selected from at least one of PEG / PPG-15 / 15 polydimethylsiloxane, PEG / PPG-18 / 12 polydimethylsiloxane, and PEG / PPG-22 / 23 polydimethylsiloxane. The function of the thixotropic agent is to enhance the interaction between powders, increase the resistance to bubble growth, prevent bubbles from merging, increase the number of pores and make them uniform, and improve the thermal insulation performance. Too little thixotropic agent will not play a corresponding role; too much thixotropic agent will make bubble growth extremely difficult, the foaming ratio will be small, and the thermal insulation performance will decrease.

[0065] In some specific embodiments of the present invention, a method for preparing a silicone ceramic foam with controllable surface thickness specifically comprises the following steps:

[0066] (1) Adding raw materials of organic silicon ceramic foam with controllable surface thickness into two planetary stirring kettles according to the raw materials of components A and B, respectively, at a temperature of 10-50° C., a revolution of 150-300 r / min, a rotation of 400-600 r / min, maintaining a negative pressure of -0.09--0.1 MPa, stirring for 2-4 hours, and respectively preparing A and B component rubber materials;

[0067] (2) mixing the A and B component rubber materials in step (1) in a mass ratio of 1:1 through a feeder, extruding the mixture between two layers of PET release films, and calendering the mixture into a sheet with a thickness of 0.5 to 2 mm;

[0068] (3) The rolled sheet is passed through an electron accelerator to irradiate the upper and lower surfaces with electrons, with an electron beam energy of 150 to 400 keV. After irradiation with a dose of 150 to 400 kGy, a skin with a thickness of 0.1 to 0.5 mm is formed on both sides of the sheet;

[0069] (4) passing the sheet irradiated with electrons in step (3) through a sulfur drying oven and performing a primary vulcanization at 40 to 80° C. for 5 to 15 minutes to complete foaming;

[0070] (5) After the primary vulcanization in step (4), the PET release film is peeled off, and the sheet is passed through a disulfide drying tunnel and subjected to secondary vulcanization molding at 150 to 180° C. for 20 to 60 minutes to obtain a silicone ceramic foam with controllable surface thickness.

[0071] The technical solution of the present invention is specifically described below by examples and comparative examples, but the present invention is not limited to these examples, and changes within the scope of the gist of the present invention are still considered to be within the scope of the rights of the present invention.

[0072] Examples 1 to 6

[0073] Embodiments 1 to 6 respectively provide a silicone ceramic foam with controllable surface thickness.

[0074] The organic silicon ceramic foams of Examples 1 to 6 are prepared by the following steps:

[0075] (1) The raw materials of the silicone ceramic foam with controllable surface thickness are added into two planetary stirring kettles according to components A and B respectively, and the temperature is controlled at 25-30°C, the revolution is 300 r / min, the rotation is 400 r / min, the negative pressure is maintained at -0.095 MPa, and the stirring is performed for 2.5 hours to prepare the A and B component rubber materials.

[0076] (2) The A and B component rubber materials in step (1) are mixed uniformly in a mass ratio of 1:1 by a feeder, and then extruded between two layers of PET release films and calendered into a sheet with a thickness of 0.5 to 2 mm.

[0077] (3) The rolled sheet is passed through an electron accelerator to irradiate the upper and lower surfaces with electrons at an energy of 150 to 400 keV. After irradiation with a dose of 150 to 400 kGy, a sheet with a cured surface is formed.

[0078] (4) The sheet obtained in step (3) is passed through a sulfur drying tunnel and subjected to a vulcanization molding at 50° C. for 10 minutes.

[0079] (5) After the primary vulcanization in step (4), the PET release film is peeled off from the sheet, and a secondary vulcanization is performed in a disulfide drying oven at 150° C. for 40 minutes to obtain a silicone ceramic foam with controllable surface thickness.

[0080] The raw material compositions of the organosilicon ceramic foams of Examples 1 to 6 are shown in Table 1, and the process parameters of the organosilicon ceramic foams of Examples 1 to 6 are shown in Table 3.

[0081] The preparation steps of Comparative Examples 1 to 7 are basically the same as those of Examples 1 to 6, except for the raw material composition, electron beam energy and irradiation dose. In addition, Comparative Example 7 does not have the step (3) of irradiation crosslinking.

[0082] The raw material compositions of the organosilicon ceramic foams of Comparative Examples 1 to 7 are shown in Table 2, and the process parameters of the organosilicon ceramic foams of Comparative Examples 1 to 7 are shown in Table 4.

[0083] Table 1 Ceramic silica foam raw material composition of Examples 1 to 6 (parts by weight)

[0084]

[0085]

[0086] Table 2 Comparative Examples 1 to 7 Ceramic Silicone Foam Raw Material Composition (Parts by Weight)

[0087]

[0088]

[0089] Description of the raw materials in Table 1 and Table 2:

[0090] The raw materials used in the examples and comparative examples of the present invention are all commercially available products.

[0091] A1~A4, Ningbo Runhe New Materials Technology Co., Ltd.;

[0092] A1: vinyl-terminated polydimethylsiloxane, viscosity 80000mP·s;

[0093] A2: vinyl-terminated polydimethylsiloxane, viscosity 20000mP·s;

[0094] A3: Vinyl-terminated polydimethylsiloxane, viscosity 2000 mP·s;

[0095] A4: vinyl-terminated polydimethylsiloxane, viscosity 200 mP·s;

[0096] The structural formula of the vinyl-terminated polydimethylsiloxane used is:

[0097]

[0098] B1: wollastonite, average particle size 5 μm, aspect ratio 5, Xinyu Siyuan Mining Co., Ltd.;

[0099] B2: muscovite powder, average particle size 7 μm, Anhui Ge Rui New Materials Technology Co., Ltd.;

[0100] B3: kaolin, particle size 325 mesh, Ningbo Jiahe New Material Technology Co., Ltd.;

[0101] B4: diatomite, particle size 10 μm, Dongguan Da Diatomite Material Co., Ltd.

[0102] C: Fumed white carbon black (i.e., fumed nano-silicon dioxide), the specific surface area measured by BET method is 200m 2 / g, Cabot DURAMOLD 2150;

[0103] D1: aluminum hydroxide, average particle size 5 μm, Hefei Zhongke Flame Retardant New Materials Co., Ltd.

[0104] D2: magnesium hydroxide, average particle size 4 μm, Hefei Zhongke Flame Retardant New Materials Co., Ltd.

[0105] D3: hydrotalcite, average particle size 5 μm, Hunan Xiongxin Innovation Materials Technology Co., Ltd.;

[0106] E: low melting point glass powder, particle size 4μm, a 1:1 mixture of two powders with melting temperatures of 430℃ and 590℃, Anmi Micro-Nano Materials (Guangzhou) Co., Ltd.;

[0107] F: Hydrogenated silicone oil, hydrogen content 1.6%, Ningbo Runhe High-tech Materials Technology Co., Ltd.;

[0108] G1: Hydroxy silicone oil, hydroxyl content 4%, Ningbo Runhe High-tech Materials Technology Co., Ltd.;

[0109] G2: isopropanol, I112011AR, purity ≥99.7%, Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0110] G3: ethanol, E130059, purity ≥99.5%, Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0111] G4: Hydroxyl silicone oil, hydroxyl content 8%, Ningbo Runhe High-tech Materials Technology Co., Ltd.;

[0112] H: Custer platinum catalyst, platinum content 5000ppm, Guangzhou Siyou New Material Technology Co., Ltd.

[0113] I: 1-hexynyl-1-cyclohexanol, purity ≥98%, Guangzhou Siyou New Material Technology Co., Ltd.;

[0114] J1: PEG / PPG-15 / 15 polydimethylsiloxane, Shanghai MacLean Biochemical Technology Co., Ltd.;

[0115] J2: PEG / PPG-18 / 12 polydimethylsiloxane, Shanghai MacLean Biochemical Technology Co., Ltd.;

[0116] J3: PEG / PPG-22 / 23 polydimethylsiloxane, Shanghai MacLean Biochemical Technology Co., Ltd.

[0117] Furthermore, the organic silicon ceramic foams prepared in Examples 1 to 6 and Comparative Examples 1 to 7 were tested as follows:

[0118] 1) Epidermal thickness:

[0119] Randomly select 3 points on the silicone ceramic foam sample and cut 3 square samples with a side length of 10±1mm. Use a digital microscope to take magnified photos of the 4 cross sections of the sample, and measure the thickness of the upper and lower skins at random points on each cross section. A total of 24 data are collected, and the average value d0 is calculated as the skin thickness of the sample.

[0120] 2)Total thickness:

[0121] Take 3 samples of (5±0.5) mm×(5±0.5) mm size and place them in an environment with a temperature of 23-27°C and a humidity of 45-55% for 2 hours. Use a vernier caliper to measure the thickness of each sample and calculate the average value.

[0122] 3) Density:

[0123] The density of the silicone ceramic foam is tested according to the standard GB / T 6343-2009.

[0124] 4) Shore A hardness:

[0125] According to the test method of A-type Shore hardness tester in GB / T 531.1-2008, the hardness A of the silicone ceramic foam is tested.

[0126] 5) Flame shock:

[0127] Take the organic silicon ceramic foam sample and make a sample of (130±10)mm×(130±10)mm size, clamp it with two stainless steel square rings of (120±2)×(120±2)mm size inside, fix it on the iron frame, adjust the flame temperature of the acetylene torch to 1300℃, and observe whether there are cracks on the back of the foam after ablation for 30 minutes. The schematic diagram of the simple device is as follows Figure 2 shown.

[0128] 6) Cold noodle temperature:

[0129] Take an appropriate amount of silicone ceramic foam sample with a thickness of ≥2mm. If the thickness is less than 2mm, use multiple layers of material to stack. Use thermal insulation performance test equipment to test the hot and cold surface temperatures at 750℃ for 5 minutes. Repeat the above test process at least 5 times and take the average value. (Guangxi Lubo Environmental Protection Technology Co., Ltd., RBC-II-30KN thermal insulation material thermal insulation performance tester)

[0130] The test results are shown in Tables 3 and 4 below.

[0131] Table 3 Performance test results of Examples 1 to 6

[0132]

[0133]

[0134] Table 4 Performance test results of comparative examples 1 to 7 It can be seen that the silicone ceramic foam with controllable skin thickness in the embodiment of the present invention has a skin thickness controlled between 0.1 and 0.5 mm, a total thickness controlled between 1 and 4 mm, and a density between 350 and 750 kg / m 3 The Shore A hardness is between 10 and 30°. Moreover, when the thickness is ≥2mm, no cracks appear on the back after 30 minutes of acetylene oxygen flame ablation at 1300°C; when the thickness is ≥2mm, the cold surface temperature of heating at 750°C for 5 minutes is ≤230°C. The ceramic silicone foam with controllable skin thickness provided in the embodiment of the present invention can meet the requirements of both flame impact performance and thermal insulation performance, and can effectively prevent fire and heat insulation in the thermal runaway environment of the battery, ensuring that personnel have precious time to safely extinguish the fire or escape from the scene.

[0135] However, one or more of the parameters of the ceramic silicone foams provided in Comparative Examples 1 to 6 are not within the scope of the present invention. These ceramic silicone foams either crack on the back side due to flame impact, or their thermal insulation performance does not meet the requirements. Among them, in Comparative Example 1, the amount of ceramic filler added is small, and the flame impact and thermal insulation effects are poor; in Comparative Example 2, the end-vinyl polydimethylsiloxane has a low viscosity, which increases the cross-linking density and has a higher hardness; at the same time, the irradiation dose is low, the epidermis is not completely cured, the epidermis is thin, the flame impact and thermal insulation effects are poor, and the hydrogen-containing silicone oil is small, which affects the foaming, resulting in a high density and poor thermal insulation performance; in Comparative Example 3, the electron beam energy is low, the penetration ability is poor, the epidermis is thin, and it is easy to crack under high temperature conditions, and the flame impact and insulation effects are poor. The thermal effect is poor; in Comparative Example 4, the electron beam energy is too high, the thickness of the skin is too thick, and ceramics are quickly formed on the surface at high temperature, but no ceramics are formed inside, resulting in a large temperature difference, the skin is prone to cracking, and the thermal runaway and thermal insulation effects are affected; in Comparative Example 5, the irradiation dose is too large, and the vinyl silicone rubber produces a small amount of decomposition, which affects the crosslinking degree of the skin layer. The skin layer has defects and is prone to forming small pores, resulting in poor thermal insulation effect; and no thixotropic agent is added, which is prone to forming large bubbles, and the hardness is too low, which affects the subsequent use performance and has no supporting capacity. In Comparative Example 6, there are too many thixotropic agents, which makes the interaction force between the filler particles too large, and it is not easy to foam, resulting in excessive density and hardness, which affects the thermal insulation effect; in Comparative Example 7, there is no irradiation crosslinking, the prepared foam skin is thin, it is easy to crack under high temperature conditions, the flame impact and thermal insulation effects are poor, and the thermal insulation effect is poor.

[0136] Therefore, the ceramic silicone foam with controllable surface thickness of the present invention has good ceramic fireproof and heat-insulating effects; at the same time, it still has excellent heat-insulating properties at high temperatures, truly achieving the fireproof and heat-insulating effects during thermal runaway of the battery.

[0137] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a silicone ceramic foam with controllable surface thickness, characterized in that: The raw materials are mixed and rolled into sheets, which are then irradiated with electrons by an electron accelerator to form a skin with a thickness of 0.1 to 0.5 mm on the outside, and then a foam structure is formed inside through primary and secondary vulcanization to obtain a silicone ceramic foam with controllable skin thickness.

2. The method for preparing the organosilicon ceramic foam with controllable surface thickness according to claim 1, characterized in that: The electron beam energy of the electron accelerator is 150-400 keV, and the irradiation dose is 150-400 kGy.

3. The method for preparing the organosilicon ceramic foam with controllable skin thickness according to claim 1, characterized in that: The temperature range of primary vulcanization is 40-80°C, and the time of primary vulcanization is 5-15 minutes.

4. The method for preparing the organosilicon ceramic foam with controllable surface thickness according to claim 1, characterized in that: The temperature range of secondary vulcanization is 150-180°C, and the time of secondary vulcanization is 20-60 minutes.

5. The method for preparing the organosilicon ceramic foam with controllable surface thickness according to any one of claims 1 to 4, characterized in that: The raw materials include vinyl-terminated polydimethylsiloxane, ceramic filler, reinforcing filler, flame retardant, flux, foaming agent, catalyst, thixotropic agent, crosslinking agent and inhibitor.

6. The method for preparing the organosilicon ceramic foam with controllable surface thickness according to claim 5, characterized in that: The raw materials include component A raw materials and component B raw materials, and the mixing mass ratio of the component A raw materials to the component B raw materials is 1:1; The raw materials of component A include: 100 parts of vinyl-terminated polydimethylsiloxane, 40-60 parts of ceramic filler, 5-20 parts of reinforcing filler, 10-20 parts of flame retardant, 10-20 parts of flux, 5-30 parts of foaming agent, 0.2-2 parts of catalyst, and 0.1-0.5 parts of thixotropic agent; The raw materials of component B include: 100 parts of vinyl-terminated polydimethylsiloxane, 40-60 parts of ceramic filler, 5-20 parts of reinforcing filler, 10-20 parts of flame retardant, 10-20 parts of flux, 10-20 parts of cross-linking agent and 0.02-0.2 parts of inhibitor.

7. The method for preparing the organosilicon ceramic foam with controllable surface thickness according to claim 6, characterized in that: The vinyl-terminated polydimethylsiloxane is a linear polymer with vinyl groups at both ends; Preferably, the vinyl-terminated polydimethylsiloxane has a viscosity of 1000 to 100000 mPa·s at 25°C.

8. The method for preparing the organosilicon ceramic foam with controllable surface thickness according to claim 6 or 7, characterized in that: The ceramic filler includes one or more of wollastonite, muscovite powder, kaolin, and diatomaceous earth; and / or, The reinforcing filler comprises one or more of fumed silica, precipitated silica, and nano calcium carbonate; and / or, The flame retardant includes one or more of magnesium hydroxide, aluminum hydroxide, and hydrotalcite; and / or, The flux comprises one or more of low melting point glass powder and zinc borate; and / or, The cross-linking agent is a hydrogen-containing silicone oil having at least three silicon-hydrogen bonds in one molecule; and / or, The foaming agent includes one or more of hydroxy silicone oil, isopropanol, and ethanol; and / or, The catalyst comprises one or more of chloroplatinic acid, a coordination compound of chloroplatinic acid and vinyl siloxane, alcohol-modified chloroplatinic acid, and a coordination compound of platinum and vinyl siloxane; and / or, The inhibitor comprises one or more of 3-methyl-1-butyn-3-ol, 1-hexynyl-1-cyclohexanol, tetramethylvinylcyclotetrasiloxane; and / or, The thixotropic agent is methyl silicone oil with a polyether structure in the side chain.

9. An organosilicon ceramic foam with controllable surface thickness, prepared by the preparation method of organosilicon ceramic foam with controllable surface thickness according to any one of claims 1 to 8, characterized in that: The thickness of the organic silicon ceramic foam is 1 to 4 mm; and / or, The density of the organic silicon ceramic foam is 350-750 kg / m 3 and / or, The Shore A hardness of the organic silicon ceramic foam is 10-30°.

10. Application of the organosilicon ceramic foam with controllable surface thickness as claimed in claim 9 in power battery cells.